Do Investors Value Dividend-Smoothing Stocks Differently? - Larkin, Yelena; Leary, Mark T.; Michaely, Roni (Management Science, 2017)
It is widely documented that managers strive to maintain smooth dividends. Yet, it is not clear if this behavior reflects investors’ preferences. In this paper, we study whether investors indeed value dividend-smoothing stocks differently by exploring the implications of dividend smoothing for firms’ investor clientele, stock prices, and cost of capital. We find that retail investors are less likely to hold dividend-smoothing stocks, while institutional investors, and especially mutual funds, are more likely. However, this preference does not result in any detectable relation between the smoothness of a firm’s dividends and the expected return, or market value, of its stock. Together, the evidence suggests that firms adjust the supply of smoothed dividends to match investors’ demand. Dividend smoothing affects the composition of a firm’s shareholders but has little impact on its stock price. This paper was accepted by Amit Seru, finance.